Wellbeing and Resilience in Tourism: A Systematic Literature Review During COVID-19 - Pocinho, Margarida; Garcês, Soraia; de Jesus, Saúl Neves (Frontiers in Psychology, 2022)
The United Nations World Tourism Organization (UWTO) has acknowledged 2020 as the worst year in tourism history due to the worldwide pandemic COVID-19. Destinations, tourists, local communities, stakeholders and residents, and their daily activities were affected. Thus, wellbeing and resilience are two crucial variables to help the industry and the people recover. This research aims to analyze early positive approaches and attitudes to respond to COVID-19 negative impact in tourism everyday activities that have at its core wellbeing and resilience, two main variables of the Positive Psychology field of studies. A systematic literature review was conducted, following PRISMA guidelines to achieve this aim. The research was done using the Online Knowledge Library (B-on) and all the available databases. The research led to 32 papers that were screened using the inclusion and exclusion criteria. A total of 18 scientific papers met all criteria. Overall, results show that a positive and resilient approach to deal with the adverse outcomes of the pandemic is a significant concern for stakeholders and the future of the organizations in the tourism and hospitality sector, as is tourists wellbeing. However, less research has been done on wellbeing and a clear lack of research regarding residents’ wellbeing and resilience is evident. A deeper study of well-being and resilience in tourism is needed, and actual practices and interventions to ensure that all tourism actors have the resources to overcome the pandemic and restart the industry's daily lives feeling well and safe.